THE ANALYSIS OF THE FORMAT AND PRESENTATION OF ENGLISH COURSE IN CURRICULUM MERDEKA - Meisya Rawenda; Rahmadi Nirwanto (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2023)
This article discusses the analysis of the format and presentation of the English course in the Merdeka Curriculum. The Merdeka Curriculum is a curriculum with an intracurricular learning system that provides teachers with the freedom to choose teaching materials according to the needs and interests of the students. English is one of the subjects programmed in the Merdeka Curriculum. The English language learning in the Merdeka Curriculum is designed to help individuals improve their speaking, listening, reading, and writing skills in English. This research adopts a library research method by collecting data and information from relevant literature sources. The collected data is analyzed through a review and understanding of existing literature. The research findings indicate that the Merdeka Curriculum provides comprehensive guidelines regarding identity, structure, teaching methods, and assessment, with a focus on flexibility in subject selection and the development of individual potential.